Combining stem cell-derived hepatocytes with impedance sensing to better predict human drug toxicity. (2nd January 2019) - Zhou, Wenli; Graham, Karen; Lucendo-Villarin, Baltasar; Flint, Oliver; Hay, David C.; Bagnaninchi, Pierre
ABSTRACT: Background : The liver plays a central role in human drug metabolism. To model drug metabolism, the major cell type of the liver, the hepatocyte, is commonly used. Hepatocytes can be derived from human and animal sources, including pluripotent stem cells. Cell-based models have shown promise in modeling human drug exposure. The assays used in those studies are normally 'snap-shot' in nature, and do not provide the complete picture of human drug exposure. Research design and methods : In this study, we employ stem cell-derived hepatocytes and impedance sensing to model human drug toxicity. This impedance-based stem cell assay reports hepatotoxicity in real time after treatment with compounds provided by industry. Results : Using electric cell-substrate impedance Sensing (ECIS), we were able to accurately measure drug toxicity post-drug exposure in real time and more quickly than gold standard biochemical assays. Conclusions : ECIS is robust and non-destructive methodology capable of monitoring human drug exposure with superior performance to current gold standard 'snapshot' assays. We believe that the methodology presented within this article could prove valuable in the quest to better predict off-target effects of drugs in humans.